Rationale of hyperthermia for radio(chemo)therapy and immune responses in patients with bladder cancer: Biological concepts, clinical data, interdisciplinary treatment decisions and biological tumour imaging - Multhoff, Gabriele; Habl, Gregor; Combs, Stephanie E. (International Journal of Hyperthermia, 2016)
Bladder cancer, the most common tumour of the urinary tract, ranks fifth among all tumour entities. While local treatment or intravesical instillation of bacillus Calmette–Guerin (BCG) provides a treatment option for non-muscle invasive bladder cancer of low grade, surgery or radio(chemo)therapy (RT) are frequently applied in high grade tumours. It remains a matter of debate whether surgery or RT is superior with respect to clinical outcome and quality of life. Surgical resection of bladder cancer can be limited by acute side effects, whereas, RT, which offers a non-invasive treatment option with organ- and functional conservation, can cause long-term side effects. Bladder toxicity by RT mainly depends on the total irradiation dose, fraction size and tumour volume. Therefore, novel approaches are needed to improve clinical outcome. Local tumour hyperthermia is currently used either as an ablation therapy or in combination with RT to enhance anti-tumour effects. In combination with RT an increase of the temperature in the bladder stimulates the local blood flow and as a result can improve the oxygenation state of the tumour, which in turn enhances radiation-induced DNA damage and drug toxicity. Hyperthermia at high temperatures can also directly kill cells, particularly in tumour areas which are poorly perfused, hypoxic or have a low tissue pH. This review summarises current knowledge relating to the role of hyperthermia in RT to treat bladder cancer, the induction and manifestation of immunological responses induced by hyperthermia, and the utilisation of the stress proteins as tumour-specific targets for tumour detection and monitoring of therapeutic outcome.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Adaptive immunity; cytotoxicity; heat shock proteins; hyperthermia; innate immunity; molecular imaging